Layers of fear: A typology of speaking anxiety among EFL proposal presenters - Basith, Ghinan Nafsiha; Fitrisia, Dohra; Fitriani, Siti Sarah; Samad, Iskandar Abdul (Englisia Journal, 2025)
English as a Foreign Language (EFL) learners frequently encounter significant challenges in developing oral proficiency, particularly within high-stakes academic contexts such as seminar proposal presentations. While speaking constitutes a fundamental dimension of language competence, many students exhibit difficulties in verbal communication despite the global prominence of English. This quantitative study investigates the speaking anxiety experienced by EFL students at UIN Ar-Raniry Banda Aceh, focusing on three distinct dimensions: communication apprehension, test anxiety, and fear of negative evaluation. Data were collected via standardized questionnaires from twelve participants across two cohorts (2017 graduates and 2021 active students), all of whom had completed seminar proposal presentations. Findings indicate that communication apprehension was the most prevalent form of anxiety, with all participants reporting moderate levels, manifested through behavioral cues such as hesitation, reduced eye contact, and note dependency. Test anxiety was also prominent, with 92% of respondents experiencing moderate symptoms, including physiological reactions (e.g., trembling, stammering) and cognitive difficulty in handling impromptu questions. In contrast, fear of negative evaluation was reported at low levels, potentially attributable to a supportive classroom environment and familiar audiences. These results underscore the multifaceted nature of speaking anxiety and its substantial influence on learner confidence in academic presentation settings. The study concludes by emphasizing the necessity for targeted pedagogical interventions designed to mitigate these affective barriers and enhance the oral communicative competence of EFL learners.